Penentuan Kadar Tanin Total Ekstrak Etanol Buah Marasi (Curculigo latifolia) Dengan Metode Spektroscopy UV-Visible - Nurahmi Lumbangaol (Program Studi S1 Farmasi, STIKES Senior, Medan, 2020)
Herbal ingredients can have potential as drugs that can be used in the health sector such as antibacterial. Tannins (Tanic Acid) are an example of a class of compounds that have the potential to be developed as herbal medicinal ingredients. Measurement of total tannin levels in this study was carried out on ethanol samples of marasi fruit (curculigo latifolia) using the Uv-Vis spectroscopy method. The sample preparation process is carried out in the stages of sorting, cleaning, washing, drying and making simplicia. The extraction method is carried out by the maceration method. The extraction results for 3 x 24 hours with a cycle of 3 times showed that the tannin content obtained from the sample was 2.09 ppm with the linearity curve obtained was y = 1.52 x + 0.015 and r2 = 0.997.